Secrets of the new Web seize the Web. - Bertolucci, Jeff.
Go beyond browsing: With these 39 exceptionally interactive Web sites and services, you can do anything from launching a private social network to publishing your own book.
Keywords: Browsers (Computer programs); Blogs; Social networks; Metacafe